Synthesizing Effective Instructional Strategies for Enhancing Speaking Skills in Primary Education: A Qualitative Meta-Synthesis of 34 Empirical Studies - Syawal Fitrah Harahap; Erna Ikawati (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2026)
This study synthesizes effective instructional strategies for enhancing speaking skills amongprimary school learners through a qualitative meta-synthesis of thirty-four empirical studies.The analysis examines convergent findings across communicative, narrative, multimodal,collaborative, and formative approaches to identify core mechanisms supporting orallanguage development. Results indicate that meaningful communicative interaction,structured narrative organization, multimodal reinforcement, peer-based collaboration, andcontinuous formative feedback collectively contribute to substantial improvements in fluency,coherence, and expressive clarity. The cross-method consistency suggests that speakingproficiency emerges not from isolated techniques but from the interplay of cognitive, affective,and social learning processes. The resulting conceptual model offers an integrated frameworkfor teachers to design holistic speaking instruction. Practically, this study highlights theimportance of interactive, multimodal, and collaborative strategies in strengtheningcommunication competence in primary education